A high lean body mass is not protecting from type 2 diabetes in the presence of a high body fat mass - Rehunen Simo K.J.; Kautiainen Hannu; Korhonen Päivi E.; Eriksson Johan G. (Elsevier Masson s.r.l., 2022)
Aim: Most studies examining the associations between body composition and type 2 diabetes have been cross-sectional with prevalent diabetes diagnosis or they have analyzed only fat or lean body mass. Hence, the combined effect of fat and lean body mass on the risk of developing type 2 diabetes remains unclear. We investigated whether baseline lean and fat body mass taken simultaneously into account are associated with incidence of type 2 diabetes over a 15-year follow-up in older adults.
Methods: We studied 704 men (n = 297) and women (n = 407) from the Helsinki Birth Cohort Study (mean age 61 years at baseline) without diabetes at baseline. Bioelectrical impedance analysis was used to derive baseline fat mass index (FMI, fat mass/height2) and lean mass index (LMI, lean mass/height2), dichotomized at sex-specific medians. Incident diabetes was defined as the composite of fasting plasma glucose (FPG) ≥ 7.0 mmol/l, haemoglobin A1c (HbA1C) ≥ 6.5% (48 mmol/mol) or physician-based diagnosis.
Results: After a median 14.8 (range 12.5-16.8) years of follow-up, 110 incident diabetes cases occurred (15.6%). Participants with high FMI and LMI at baseline had higher composite incidence of type 2 diabetes (P < 0.001), and significantly increased risk of type 2 diabetes after adjustment for potential confounding factors (sex, physical activity, education and body mass index) compared to the other participants.
Conclusion: Contrary to a general belief greater muscle mass is not protective against type 2 diabetes. High LMI accompanied with high FMI seem to predict subsequent development of type 2 diabetes.